1999
DOI: 10.1111/j.1445-5994.1999.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐transglutaminase antibodies and coeliac disease

Abstract: Our results demonstrated the sensitivity and specificity of IgA anti-tissue transglutaminase antibodies to correlate highly with anti-endomysial antibodies in the diagnosis of coeliac disease. The ELISA for IgA anti-tissue transglutaminase antibodies is quantitative and easy to perform and is a valid alternative to indirect immunofluorescence for anti-endomysial antibodies in screening for suspected coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…The human recombinant tTG-based ELISA is a sensitive, specific, and reproducible test to support the diagnosis and follow-up of childhood celiac disease and can be used as an alternative to the EMA test. However, further study remains to be undertaken to determine whether the use of recombinant human tTG can accurately detect 100% of the celiac patients (20,35,36) and thereby to which extent it might in the future replace intestinal biopsy for diagnosis of celiac disease in childhood. …”
Section: Discussionmentioning
confidence: 99%
“…The human recombinant tTG-based ELISA is a sensitive, specific, and reproducible test to support the diagnosis and follow-up of childhood celiac disease and can be used as an alternative to the EMA test. However, further study remains to be undertaken to determine whether the use of recombinant human tTG can accurately detect 100% of the celiac patients (20,35,36) and thereby to which extent it might in the future replace intestinal biopsy for diagnosis of celiac disease in childhood. …”
Section: Discussionmentioning
confidence: 99%
“…Because of the varied clinical presentations of CD, serological methods have been found to be very useful for detecting its existence in patients with thyroid autoimmunity. This association has been the subject of several investigations (5,37,38,49,65,70,73,89,96,113) (Table 2). These studies include determining the occurrence of CD in thyroid patients, whereas other investigations focused on the incidence of thyroid autoimmunity in patients with CD.…”
Section: Autoimmune Endocrine Disorders and CDmentioning
confidence: 99%
“…Three thyroid diseases are considered to have autoimmune etiology: Hashimoto's thyroiditis, idiopathic myxedema, and Grave's disease. The antigens against which the autoimmune reactions are directed to produce thyroid autoimmune disease include thyroglobulin (Tg), thyroid peroxidase (TPO), and the TSH receptor (5,37,38,49,65,70,73,89,96,113). These autoantibodies cause direct thyroid dysfunction, as in Grave's disease caused by antibodies to the TSH receptor, or a destructive process, as in Hashimoto's thyroiditis and idiopathic myxedema.…”
Section: Autoimmune Endocrine Disorders and CDmentioning
confidence: 99%
“…In addition, IgA endomysial antibodies are more sensitive and specific than either reticulin or gliadin IgA antibodies for diagnosis of GSE (5,(9)(10)(11)(12)(13). Since the discovery of the role of tTG as the autoantigen in celiac disease (7), studies have shown a high degree of correlation between IgA anti-tTG and IgA EMA in patients with GSE (14)(15)(16)(17). IgA EMA has been reported to be a more sensitive assay, particularly during gluten challenge (18).…”
Section: Discussionmentioning
confidence: 99%